2019
DOI: 10.1523/jneurosci.2745-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

X-Chromosome Insufficiency Alters Receptive Fields across the Human Early Visual Cortex

Abstract: Here, we investigated processing by receptive fields, a fundamental property of neurons in the visual system, using fMRI and population receptive field (pRF) mapping in 20 human females with monosomic Turner syndrome (TS) (mean age, 10.3 Ϯ 2.0 years) versus 22 ageand sex-matched controls (mean age, 10.4 Ϯ 1.9 years). TS, caused by X-chromosome haploinsufficiency in females, is associated with well-recognized effects on visuospatial processing, parieto-occipital cortical anatomy, and parietal lobe function. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…We verify the feasibility of this prediction with CXorf58 (Fig 3), an X chromosome gene whose expression negatively correlated with eccentricity and has been linked to retinitis pigmentosa (RP), which results in perceptual deficits of the peripheral visual field. Mutations in CXorf58 may also explain recent findings 9 showing that females with Turner Syndrome (TS) -a condition in which an X chromosome is damaged or missing 10 -present with deficits in RF coverage of the peripheral visual field specifically in V2 and V3, where CXorf58 is negatively correlated with eccentricity ( Fig 3). Additional mutations in SLITRK4 and RAI2 -both X chromosome genes involved in axonogenesis 11 and cell growth 12 and identified here -could adversely impact peripheral representations where tissue microstructure reductions would hinder the fidelity of neural circuits underlying the pooling of visual information.…”
Section: Figure 1: Opposing Transcriptomic Gradients Explain Orthogonmentioning
confidence: 86%
See 1 more Smart Citation
“…We verify the feasibility of this prediction with CXorf58 (Fig 3), an X chromosome gene whose expression negatively correlated with eccentricity and has been linked to retinitis pigmentosa (RP), which results in perceptual deficits of the peripheral visual field. Mutations in CXorf58 may also explain recent findings 9 showing that females with Turner Syndrome (TS) -a condition in which an X chromosome is damaged or missing 10 -present with deficits in RF coverage of the peripheral visual field specifically in V2 and V3, where CXorf58 is negatively correlated with eccentricity ( Fig 3). Additional mutations in SLITRK4 and RAI2 -both X chromosome genes involved in axonogenesis 11 and cell growth 12 and identified here -could adversely impact peripheral representations where tissue microstructure reductions would hinder the fidelity of neural circuits underlying the pooling of visual information.…”
Section: Figure 1: Opposing Transcriptomic Gradients Explain Orthogonmentioning
confidence: 86%
“…While the condition is hallmarked by a number of physical atypicalities, genes on the short arm of the X chromosome (e.g., short stature homeobox gene, SHOX) have been linked to the stunted bone and limb growth that characterizes the small stature of those with Turner syndrome. Recent research has demonstrated that females with Turner syndrome present with visual deficits in the coverage of the periphery 9 . Retinotopic mapping of population receptive fields (pRF) in these individuals using functional MRI revealed that in V2 and V3, Turner females show reduced pRF coverage of the periphery compared to control females.…”
Section: Intra-regional Genes On the X Chromosomementioning
confidence: 99%
“…The population receptive field (pRF) mapping technique (Dumoulin and Wandell, 2008) has rapidly become a popular method in human neuroimaging, allowing a relatively fast characterization of the retinotopic organization of the brain. Furthermore, since it describes the tuning properties of the underlying voxels, it can also provide insight into more complex visual and cognitive functions (Binda et al, 2018;Ekman et al, 2020;Harvey et al, 2020Harvey et al, , 2015He et al, 2019;Hughes et al, 2019;Mo et al, 2017;Poltoratski et al, 2019;Poltoratski and Tong, 2020;Shao et al, 2013;Shen et al, 2020;Silson et al, 2018;Stoll et al, 2020;Thomas et al, 2015;Welbourne et al, 2018;Zuiderbaan et al, 2017), dysfunctions (Ahmadi et al, 2020;Alvarez et al, 2020;Best et al, 2019;Dumoulin and Knapen, 2018;Green et al, 2019;Schwarzkopf et al, 2014), brain development (Dekker et al, 2019), cortical evolution (Zhu and Vanduffel, 2019), and information transfer across different brain areas (Haak et al, 2013). Human pRFs from neuroimaging studies qualitatively resemble receptive fields recorded with invasive electrophysiological techniques in animal experiments, but since these signals are derived from different species, often with different analytical or experimental methods, it remains an important question what type of neuronal population characteristic is actually measured by the fMRI BOLD-signal (Dumoulin and Wandell, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…5). The possibility that group effects could mask effects at the individual subject level is also applicable to any study comparing the functional or structural organization of cortical areas between two or more groups -for example, comparing functional representations between a) children and adults (Cantlon et al, 2006;Golarai et al, 2007;Scherf et al, 2007b;Deen et al, 2016) or b) between neurotypical controls and individuals in a clinical population (Temple et al, 2001;Avidan et al, 2005;Duchaine and Nakayama, 2005;Rykhlevskaia et al, 2009;Green et al, 2019bGreen et al, , 2019a. Future studies can also quantify how different types of stimuli such as soundscapes (Amedi et al, 2007) or haptic substitution (Amedi et al, 2001;Pascual-leone et al, 2005;Reich et al, 2011;Murty et al, 2020) influence individual differences in the blind.…”
Section: Implications For Future Studiesmentioning
confidence: 99%
“…An individual differences hypothesis predicts that irrespective of group-level differences, category representations are significantly more heterogenous among group members to the point that there are similarities between individuals across groups that are larger than similarities between individuals within a group. Empirically supporting either hypothesis has implications for future studies comparing populations at the group and individual level (Temple et al, 2001;Avidan et al, 2005;Duchaine and Nakayama, 2005;Cantlon et al, 2006;Golarai et al, 2007;Scherf et al, 2007a;Rykhlevskaia et al, 2009;Deen et al, 2016;Green et al, 2019bGreen et al, , 2019a .…”
Section: Introductionmentioning
confidence: 96%